Numerical Simulation of Air Entrainment for Flat-Sloped Stepped Spillway. (March 2015) - Chakib, Bentalha; Mohammed, Habi
Stepped spillway is a good hydraulic structure for energy dissipation because of the large value of the surface roughness. The performance of the stepped spillway is enhanced with the presence of air that can prevent or reduce the cavitation damage. Chanson developed a method to determine the position of the start of air entrainment called inception point. Within this work the inception point is determined by using fluent computational fluid dynamics (CFD) where the volume of fluid (VOF) model is used as a tool to simulate air-water interaction on the free surface thereby the turbulence closure is derived in the k –ε turbulence standard model, at the same time one-sixth power law distribution of the velocity profile is verified. Also the pressure contours and velocity vectors at the bed surface are determined. The found numerical results agree well with experimental results.